IMPLEMENTATION OF THE P5–PPRA MODEL IN PRESERVING GAYONESE CULTURAL IDENTITY IN CENTRAL ACEH MADRASAHS - Tathahira Tathahira (Jurnal As-Salam, 2026)
The implementation of the Merdeka Curriculum in madrasahs requires the integration of the Pancasila Student Profile (P5) with the Rahmatan lil ‘Alamin Student Profile (PPRA), particularly within local cultural contexts. However, limited studies have examined how the P5–PPRA model is implemented in culturally distinctive regions such as Central Aceh. This study aims to analyze the implementation levels of the Merdeka Curriculum and the design of local wisdom-based P5–PPRA projects in three madrasahs: MAN 2 Aceh Tengah, MTsN 1 Aceh Tengah, and MIN 8 Aceh Tengah. Using a descriptive qualitative approach, data were collected through in-depth interviews with six participants (three principals and three teachers). The findings reveal three levels of curriculum implementation: mandiri belajar, mandiri berubah, and mandiri berbagi. Key challenges include teacher readiness, varying pedagogical interpretations, and limited supporting resources. The local wisdom projects emphasize Gayo language revitalization, traditional culinary practices, and cultural dances. This study highlights the originality of integrating the P5–PPRA framework with Gayo cultural preservation and provides practical implications for culturally responsive curriculum implementation in madrasahs.